Granuloma Transplantation: An Approach to Study Mycobacterium–Host Interactions - Harding, Jeff S.; Scheiber, Heidi; Sandor, Matyas (Frontiers in Microbiology, 2011)
The host-pathogen biology during infection with Mycobacterium tuberculosis is incredibly complex and despite accelerating progress in research, remains poorly understood. Our limited understanding hinders the development of new drugs, next generation vaccines, and novel therapies. The granuloma is the site where mycobacteria are both controlled and allowed to persist, but it remains one of the least studied aspects of the host-pathogen relationship. Here, we review the development, application, potential uses, and limitations of a novel model of granuloma transplantation as a tool to study specific host-pathogen interactions that have been difficult to probe. Application of this new model has already contributed to our understanding of granuloma cell traffic, repopulation, and the relationship between systemic immunity and mycobacteria-containing granulomas. The data collected highlight the dynamic interaction between systemic and local immune processes and support a paradigm that defines the granuloma as a highly dynamic structure. Granuloma transplantation also has special potential as a novel latency model that can contribute to our understanding of host protection factors and bacterial mutants, and serve as a platform for drug testing.